Autophagy governs protumorigenic effects of mitotic slippage-induced senescence - Jakhar, Rekha (2020)
The most commonly utilized class of chemotherapeutic agents administered as a first-line therapy are antimitotic drugs; however, their clinical success is often impeded by chemoresistance and disease relapse. Hence, a better understanding of the cellular pathways underlying escape from cell death is critical. Mitotic slippage describes the cellular process where cells exit antimitotic drug-enforced mitotic arrest and "slip" into interphase without proper chromosome segregation and cytokinesis. The current report explores the cell fate consequence following mitotic slippage and assesses a major outcome following treatment with many chemotherapies, therapy-induced senescence. It was found that cells postslippage entered senescence and could impart the senescence-associated secretory phenotype (SASP). SASP factor production elicited paracrine protumorigenic effects, such as migration, invasion, and vascularization. Both senescence and SASP factor development were found to be dependent on autophagy. Autophagy induction during mitotic slippage involved the autophagy activator AMPK and endoplasmic reticulum stress response protein PERK. Pharmacologic inhibition of autophagy or silencing of autophagy-related ATG5 led to a bypass of G1 arrest senescence, reduced SASP-associated paracrine tumorigenic effects, and increased DNA damage after S-phase entry with a concomitant increase in apoptosis. Consistent with this, the autophagy inhibitor chloroquine and microtubule-stabilizing drug paclitaxel synergistically inhibited tumor growth in mice. Sensitivity to this combinatorial treatment was dependent on p53 status, an important factor to consider before treatment.Implications: Clinical regimens targeting senescence and SASP could provide a potential effective combinatorial strategy with antimitotic drugs.